Dynamics of plasma micronutrient concentrations and their correlation with serum proteins and thyroid hormones in patients with paracoccidioidomycosis. - Jeniffer Michelline de Oliveira Custódio; Iasmim Mayumi Enokida; Daniel Araujo Gonçalves; Sandra Maria do Valle Leone de Oliveira; James Venturini; Lidia Raquel Carvalho; Rinaldo Poncio Mendes; Anamaria Mello Miranda Paniago (PLoS ONE, 2019)
Minerals, such as zinc, copper, and iron are reported to play roles in chronic infectious diseases; however, their role in paracoccidioidomycosis (PCM) remains unknown. This study aimed to examine the micronutrient dynamics and their correlation with serum proteins and thyroid hormones in patients with PCM. In 14 patients with PCM and 10 healthy subjects, we evaluated the body mass index (BMI) along with serum levels of hemoglobin, iron, ferritin, zinc, copper, magnesium, albumin, globulin, thyroid stimulating hormone (TSH), thyroxine (free T4), and triiodothyronine (T3). Evaluations were conducted at the first appointment, before treatment, and at the end of the first, second, fourth, and sixth month of PCM treatment. The control group was only evaluated once. We observed that before treatment, patients with PCM, had higher levels of copper and lower level of iron than those of the control group. After one month of treatment, the iron levels increased, whereas the levels of copper after six months of treatment. Reduction in inflammatory activity, indicated by the normalization of C-reactive protein, ferritin, albumin, and globulin levels, was observed during treatment. However, no correlation was observed between the serum levels of minerals and inflammatory activity or thyroid function in this study. In conclusion, our results showed higher serum copper levels in control group compared to those in pretreatment patients; the clinical importance of this observation should be investigated in further studies. After treatment, serum copper levels showed a tendency to decrease. In addition, serum iron levels were decreased at the stage of active disease, and were increased after treatment. Thus, serum iron levels can be used as a better biomarker for treatment control.